2015
DOI: 10.1124/mol.115.101451
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hsp90 Inhibitor Activates Compensatory Heat Shock Protein Responses and Autophagy and Alleviates Mutant A53Tα-Synuclein Toxicity

Abstract: A potential cause of neurodegenerative diseases, including Parkinson's disease (PD), is protein misfolding and aggregation that in turn leads to neurotoxicity. Targeting Hsp90 is an attractive strategy to halt neurodegenerative diseases, and benzoquinone ansamycin (BQA) Hsp90 inhibitors such as geldanamycin (GA) and 17-(allylamino)-17-demethoxygeldanamycin have been shown to be beneficial in mutant A53T a-synuclein PD models. However, current BQA inhibitors result in off-target toxicities via redox cycling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…By measuring LC3-II levels as a functional reporter of autophagy [48, 49], we first, transiently transfected SKBR3 with GFP-LC3 for 18 hours and scored by immunofluorescence the number of LC3 dots under different treatment conditions. We found that GA treatment reduced the number of LC3-II dots within cells (Figure 8A-8C), suggesting that HSP90 inhibition suppresses autophagy in contrast to previous studies in different experimental settings [50, 51]. To assess whether the LC3-II reduction resulted from either decreased autophagosomes synthesis, or from an increased degradation, we evaluated the autophagic flux in the presence of Baf, that is known to block autophagosome degradation [49, 52].…”
Section: Resultsmentioning
confidence: 87%
“…By measuring LC3-II levels as a functional reporter of autophagy [48, 49], we first, transiently transfected SKBR3 with GFP-LC3 for 18 hours and scored by immunofluorescence the number of LC3 dots under different treatment conditions. We found that GA treatment reduced the number of LC3-II dots within cells (Figure 8A-8C), suggesting that HSP90 inhibition suppresses autophagy in contrast to previous studies in different experimental settings [50, 51]. To assess whether the LC3-II reduction resulted from either decreased autophagosomes synthesis, or from an increased degradation, we evaluated the autophagic flux in the presence of Baf, that is known to block autophagosome degradation [49, 52].…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies that reported induction of autophagy by HSP90 inhibition relied mainly on accumulation of LC3-II, the ratio of LC3-II:LC3-I (as assessed by immunoblotting), and/or on an enhanced LC3 punctate appearance in treated cells. [46][47][48][49] Those studies did not monitor for autophagic flux, or incorrectly interpreted results obtained in the presence of lysosomal inhibition. 32,49 The autophagic repression documented in this study, is mediated by the downregulation of ATG7, and is demonstrated by both autophagy-specific assays and general measures of lysosomal activity.…”
Section: Discussionmentioning
confidence: 99%
“…HSP90 has been recently identified as the predominant chaperone implicated in α-synuclein-induced PD pathologies [36,37], which could prevent α-synuclein misfolding, oligomerization, and aggregation to suppress α-synuclein misfolding-induced PD toxicity [38]. In addition, HSP90 could regulate the proliferative and senescent client proteins [14], including PI3K, AKT, MAPKs, CDK4, Cyclin D1, and VEGF, which also indicated that HSP90 played an important role in the PD [24,25,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HSP90 could regulate the proliferative and senescent client proteins [14], including PI3K, AKT, MAPKs, CDK4, Cyclin D1, and VEGF, which also indicated that HSP90 played an important role in the PD [24,25,38,39]. Quantitative proteomics technique is a reliable and precise method to predict the disease-specific targets and underlying mechanism [21].…”
Section: Discussionmentioning
confidence: 99%